2015
DOI: 10.14254/2071-789x.2015/8-2/13
|View full text |Cite
|
Sign up to set email alerts
|

Ex-post Analysis of the EU Emission Trading in Year 2013 in the Czech Republic

Abstract: ABSTRACT. The main goal of the paper is to provide the first ex-post analysis of the EU ETS in year 2013 in the Czech Republic, based on the analysis of the key EU ETS sector -combustion processes. Regarding the methodology, the empirical research was used as a one part, as a second part the Mamdani fuzzy rule-based system. Since the EUA market price was low in year 2013, the Czech companies within the combustion processes group had weak motivation to trade with the EUAs. However, the revenues obtained from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This method was employed by Schimel [11] to measure the carbon emissions in some major countries in the 1980s, a study that concluded that 78% of the global carbon emissions are caused by the burning of fossil fuels and cement production. In addition to the above-mentioned methods, there are also many other methods for the measurement of carbon emissions, such as factor-decomposition analysis, the Kaya Model, and the method of carbon footprint, which have been used by recent researchers such as Kasperowicz [12], Zimmermannová et al [13], Stavytskyy et al [14], and Straczewska [15].…”
Section: The Measurement Of Carbon Emissionmentioning
confidence: 99%
“…This method was employed by Schimel [11] to measure the carbon emissions in some major countries in the 1980s, a study that concluded that 78% of the global carbon emissions are caused by the burning of fossil fuels and cement production. In addition to the above-mentioned methods, there are also many other methods for the measurement of carbon emissions, such as factor-decomposition analysis, the Kaya Model, and the method of carbon footprint, which have been used by recent researchers such as Kasperowicz [12], Zimmermannová et al [13], Stavytskyy et al [14], and Straczewska [15].…”
Section: The Measurement Of Carbon Emissionmentioning
confidence: 99%